La communication conflictuelle (Altre Modernità, 2010)
Society is based upon the exchange and the sharing of ideas in order to build common opinions, symbols and representations; nevertheless violent confrontations often mark social communication. For this reason, understanding the social communication clashes could give a better comprehension of the whole society and particularly of its political life. Controversy implies close attention to one's opponent's words.  Polemic discourse analysis tends then to consider how others' words and speeches are repeated, distorted or even manipulated. On the other hand, the degree of violence is conveyed in several kinds of speeches, the typology of which lets social intercourse be dealt with.